Identification of New Virulence Factors and Vaccine Candidates for Yersinia pestis - Andersson, Jourdan A.; Sha, Jian; Erova, Tatiana E.; Fitts, Eric C.; Ponnusamy, Duraisamy; Kozlova, Elena V.; Kirtley, Michelle L.; Chopra, Ashok K. (Frontiers in Cellular and Infection Microbiology, 2017)
Earlier, we reported the identification of new virulence factors/mechanisms of Yersinia pestis using an in vivo signature-tagged mutagenesis (STM) screening approach. From this screen, the role of rbsA, which encodes an ATP-binding protein of ribose transport system, and vasK, an essential component of the type VI secretion system (T6SS), were evaluated in mouse models of plague and confirmed to be important during Y. pestis infection. However, many of the identified genes from the screen remained uncharacterized. In this study, in-frame deletion mutants of ypo0815, ypo2884, ypo3614-3168 (cyoABCDE), and ypo1119-1120, identified from the STM screen, were generated. While ypo0815 codes for a general secretion pathway protein E (GspE) of the T2SS, the ypo2884-encoded protein has homology to the βγ crystallin superfamily, cyoABCDE codes for the cytochrome o oxidase operon, and the ypo1119-1120 genes are within the Tol-Pal system which has multiple functions. Additionally, as our STM screen identified three T6SS-associated genes, and, based on in silico analysis, six T6SS clusters and multiple homologs of the T6SS effector hemolysin-coregulated protein (Hcp) exist in Y. pestis CO92, we also targeted these T6SS clusters and effectors for generating deletion mutants. These deletion mutant strains exhibited varying levels of attenuation (up to 100%), in bubonic or pneumonic murine infection models. The attenuation could be further augmented by generation of combinatorial deletion mutants, namely ΔlppΔypo0815, ΔlppΔypo2884, ΔlppΔcyoABCDE, ΔvasKΔhcp6, and Δypo2720-2733Δhcp3. We earlier showed that deletion of the lpp gene, which encodes Braun lipoprotein (Lpp) and activates Toll-like receptor-2, reduced virulence of Y. pestis CO92 in murine models of bubonic and pneumonic plague. The surviving mice infected with ΔlppΔcyoABCDE, ΔvasKΔhcp6, and Δypo2720-2733Δhcp3 mutant strains were 55-100% protected upon subsequent re-challenge with wild-type CO92 in a pneumonic model. Further, evaluation of the attenuated T6SS mutant strains in vitro revealed significant alterations in phagocytosis, intracellular survival in murine macrophages, and their ability to induce cytotoxic effects on macrophages. The results reported here provide further evidence of the utility of the STM screening approach for the identification of novel virulence factors and to possibly target such genes for the development of novel live-attenuated vaccine candidates for plague.